2017
DOI: 10.5603/arm.2017.0060
|View full text |Cite
|
Sign up to set email alerts
|

Kyphoscoliosis—What Can We Do for Respiration besides NIV?

Abstract: Kyphoscoliosis (KS) is a significant clinical problem with no precise guidelines for management, especially concerning respiratory pathology. No exhaustive systematic review has yet been performed. The aim was to conduct a systematic review of available data concerning the pathophysiology and treatment of kyphoscoliosis. An electronic systematic search compliant with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was conducted. The Pubmed database was examined and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It is known that no other respiratory failure treatment method in kyphoscoliosis is more effective than NIV [27]. Such treatment in patients with kyphoscoliosis not only increases the survival rate [28], but also improves gasometry, reduces hypoventilation symptoms and has a beneficial impact on muscle function [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that no other respiratory failure treatment method in kyphoscoliosis is more effective than NIV [27]. Such treatment in patients with kyphoscoliosis not only increases the survival rate [28], but also improves gasometry, reduces hypoventilation symptoms and has a beneficial impact on muscle function [29].…”
Section: Discussionmentioning
confidence: 99%
“…Kyphoscoliosis is linked to varying degrees of cardiopulmonary deterioration; the development of PH marks a more severe outcome. Although the first reports on kyphoscoliosis complicated by PH appeared several decades ago, the amount of publications reporting novel therapeutic approaches remains scarce [6]. A recent registry study of adult PH patients reported that none of the 1344 enrolled participants were affected by kyphoscoliosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…It can develop at any age but manifests clinically during periods of rapid growth. In general populations, its prevalence varies from 0.3% to 15.3% with a female preponderance [Female: male ratio 3:1] [1] .…”
Section: Introductionmentioning
confidence: 99%